Xanthogranuloma in the heavily irradiated low neck in a patient with head and neck cancer. Issue 1 (December 2016) - Singer, Lisa; Calkins, Sarah; Horvai, Andrew; Ryan, William; Yom, Sue
Abstract Background Head and neck cancer is often managed with a combination of surgery, radiation therapy, and chemotherapy, and skin toxicity is not uncommon. Xanthogranuloma is a pathological finding resulting from an inflammatory reaction that has not been previously reported following head and neck radiation therapy. Case presentation A patient with squamous cell carcinoma of the oropharynx, treated with definitive chemoradiation and hyperthermia, presented at eight-month follow-up with an in-field cutaneous lesion in the low neck, initially concerning for recurrent tumor. Biopsy showed xanthogranuloma and the patient underwent complete resection with congruent surgical pathology. The patient remained free of malignancy but continued to experience wound healing difficulties at the resection site which resolved with specialized wound care and hyperbaric oxygen. Conclusions Skin toxicity is not uncommon in patients with head and neck cancer treated with radiation therapy. Awareness of unusual pathologic sequelae, such as xanthogranuloma, is needed to provide patient counseling while continuing appropriate surveillance for recurrent malignancy.